Effect of air properties on a twin-shaft turbofan engine performance during start-up. (5th January 2023) - Wang, Zhitao; Zhang, Jingkai; Gao, Chuming; Ming, Liang
Highlights: A novel method for calculating transient performance of start-up phase is presented. Low speed lines are generated considering humidity correction. Effects of ambient humidity and temperature on matching process of turbofan engine and starter in the start-up stage are studied. Abstract: When engines start in coastal areas in summer, the performance of turbofan engine and starter will be inevitably affected by ambient humidity and temperature. It is important to predict the change of start-up performance by capturing the effect of ambient humidity and temperature on the matching process between turbofan engine and starter. However, in the start-up model, starter model is usually simplified by look-up table of starter power and semi-empirical formulas. It is difficult to simulate the variation of transient performance of turbofan engine caused by the power change of the starter when the ambient humidity and temperature increase. In this paper, a new method for simulating the transient performance of start-up process is presented. The nonlinear transient model including turbofan engine and starter is developed based on real engine configurations. The power compatibility equation is established to correlate the turbofan engine and starter to predict the matching performance in the start-up stage. The model is validated using mature commercial software. The steady-state errors of the model are within 2 % and the dynamic errors are within 2.5 %. In this paper, the start-up process is divided into four stages, and the transient performance of turbofan engine and starter in each stage is analyzed. This paper simulates the transient performance of start-up process under different ambient temperature and humidity conditions. The results show that when the ambient temperature is 308.5 K and the relative humidity is 0.8, the starter power is reduced by 76.86 % and the start-up time is increased by 10.28 s.